Aplikasi Fasies Sedimen Fluviatil terhadap Perubahan Iklim Global (Studi Kasus: ”Geologi Kuarter Dataran Aluvium Rawa Utara Betung, Kabupaten Banyuasin, Sumatera Selatan” ) - Moechtar, Herman (Jurnal Geologi dan Sumberdaya Mineral, 2006)
The Quaternary deposits in the studied area comprise sand of fluvial origines, separated by clay deposits of swamp, backswamp, and floodplain. The fluvial channel was characterized by the increase and decrease of axial bodies. Vertically, the character of fine-grained deposits showed the changing in colour and percentage of humic and peat contents. Differences in the amount of clastic supply was caused by the changes in climatological conditions. Climate is an important and independent force in controlling the weathering, erosion, and sediment supply to Quaternary deposits of swampy alluvial basin. A systematic change in the type of fluvial system on the swampy alluvial plain could be the result of the changes in the sediment supply and ratio between coarse-grained bedload and suspended load. It means, the sedimentary processes on the basin can develop under the condition of climatic changes. Key words: Quaternary deposit, fluvial, swamp, climate